Symbiont starvation affects the stability of the coral–Symbiodiniaceae symbiosis - Martinez, Stephane; Grover, Renaud; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2022)
Coral bleaching, the breakdown of the coral-Symbiodiniaceae association has been identified as a major cause of coral reef decline worldwide. When symbiont functions are compromised, corals receive fewer photosynthetic products from their symbionts and suffer significant starvation along with changes in nutrient cycling. Not all coral species are equally susceptible to bleaching, but despite intensive research, our understanding of the causes for coral bleaching remains incomplete. Here, we investigated nutrient exchange between host and symbionts of two coral- Symbiodiniaceae associations that are differentially susceptible to bleaching when maintained under heterotrophy in the dark. We followed the fate of heterotrophic nutrients using bulk isotope and compound-specific (amino acid) isotope analyses. We showed that symbiont starvation is a major cause of symbiotic breakdown in the dark. While Oculina patagonica transferred almost all heterotrophically-acquired amino acids within two weeks in the dark to its symbionts and did not bleach, Turbinaria reniformis, transferred only 2 amino acids to its symbionts after 4 weeks in the dark, and experienced significant bleaching. These results pave the way for future studies on the role of nutrition in coral stress response and the importance of maintaining a healthy symbiont population to avoid coral bleaching.